Khulafah Al-Rasyidun: Menelaah Kepemimpinan Abu Bakar Al-Shiddiq - Ahmad Yani (CARITA: Jurnal Sejarah dan Budaya, 2022)
This paper aims to reveal and explain the history of the leadership of the caliph Abu Bakar Al-Shiddiq, a very close friend of the Prophet Muhammad. In revealing and explaining the leadership of Abu Bakr Ash-Siddiq the author proposes two background problems, namely (1) how is the process of appointing Abu Bakar Al-Shiddiq as caliph? (2) What are the prominent policies adopted by Abu Bakar As-Siddiq during his reign? To answer the background of the problem, a historical method is used which includes four stages of work systematically, namely: heuristics, source criticism, interpretation and historiography.The results of the study show that Abu Bakar Al-Shiddiq was a friend of the Prophet Muhammad SAW who was entrusted by the Muslims to lead Muslims after the death of the Prophet Muhammad. During his reign there were many challenges faced. Among the challenges faced are many Muslims who are apostates and do not want to pay zakat; false prophets appeared, and the territory of the Muslims was threatened by the Romans in the north (Sham). However, Caliph Abu Bakar was able to deal with all these problems wisely. Tulisan ini bertujuan untuk mengungkapkan dan menjelaskan sejarah kepemimpinan khalifah Abu Bakar Ash-Shiddiq, sahabat yang sangat dekat dengan Rasulullah SAW. Dalam mengungkapkan dan menjelaskan kepemimpinan Abu Bakar Ash-Shiddiq penulis mengajukan dua latar masalah yaitu (1) bagaimana Bagaimana proses pengangkatan Abu Bakar Al-Shiddiq menjadi khalifah? (2) Apa saja kebijakan menonjol yang ditempuh Abu Bakar Al-Shiddiq pada masa pemerintahannya? Untuk menjawab latar masalah tersebut digunakan metode sejarah yang meliputi empat tahapan kerja secara sistematis, yaitu: heuristik, kritik sumber, interpretasi dan historiografi. Hasil kajian menunjukkan bahwa Abu Bakar Al-Shiddiq merupakan seorang sahabat Nabi Muhammad SAW yang dipercayakan oleh kaum muslimin untuk memimpin umat Islam pasca wafatnya Nabi Muhammad SAW. Pada masa pemerintahannya terdapat banyak tantangan yang dihadapi. Di antara tantangan yang dihadapi adalah banyak kaum muslimin yang murtad dan tidak mau membayar zakat; muncul nabi-nabi palsu, dan wilayah umat Islam terancam oleh Romawi di bagin utara (Syam). Namun, Khalifah Abu Bakar mampu mengatasi semua masalah tersebut dengan bijaksana.